The European Convention on Human Rights: A Central and Eastern European Perspective (Human Rights – Children’s Rights, 2026)
The volume gives an overview, article by article, of the European Convention on Human Rights and its additional protocols, which are not included in the text of the Convention but are directly applicable. The introductory chapters present the aims of the foundation of the Council of Europe, and how it developed into a complex intergovernmental organisation. It describes its adoption, structure, content, protocols and the doctrines developed by the European Court of Human Rights. They present also the incorporation of the Convention at the domestic level, its impact on the national legal systems and its role in the constitutional order of Europe. The volume describes also the institutional framework of the Court. It demonstrates how the structure of the Court changed after the adoption of the additional protocols, namely Protocol 11 (abolition of the Commission, rules regarding the judges, the tasks of the different formations of the Court, admissibility criteria, third-party intervention, friendly settlements, and public hearings), Protocol 14 (terms of office of the judges to nine years and no re-election, single-judge formation to declare applications inadmissible) and Protocol 15 (principle of subsidiarity and the margin of appreciation doctrine), and describes the current institutional structure, and Protocol 16 (advisory opinion). The chapters dealing with the individual human rights are structured according to the articles of the Convention. Following an introduction (which covers the circumstances surrounding the creation of the provision in question), each discusses the scope and content of the protected right, the relevant case law of the Court up to the most recent judgments, the negative and positive obligations incumbent on states, and the relationship between the right in question and other rights. The provisions of the Convention relating to the procedure and institution of the Court are also analysed. And each chapter focuses on the implementation of the Convention in Central and Eastern European countries.